The genus Triomicrus Sharp from central and southwestern China (Coleoptera: Staphylinidae: Pselaphinae), and a revised key to the Chinese species - Shen, Jia-Wei; Yin, Zi-Wei (Zootaxa, 2016)
Five species of the genus Triomicrus Sharp from central and southwestern China are recognized, two of them are described as new: T. mangshanensis sp. n. from Hunan, and T. nabanhensis sp. n. from Yunnan. New distributional records for T. ludificator Löbl, Kurbatov & Nomura, T. mirus Shen & Yin, and T. punctifrons Löbl, Kurbatov & Nomura are given. A revised key to the Triomicrus species of China is presented.